Pituitary macroadenoma with optic chiasm compression and hypopituitarism: a case report - Alexander Kam; Dinda Aprilia; Eva Decroli (Faculty of Medicine, Universitas Trisakti, 2026)
INTRODUCTIONPituitary macroadenomas are benign pituitary tumors measuring more than 1 cm in diameter that constitute a substantial proportion of intracranial neoplasms. Despite their benign histology, these tumors may lead to significant morbidity due to local mass effects and endocrine dysfunction. Compression of the optic chiasm can result in progressive visual impairment and irreversible blindness if not promptly treated. Additionally, pituitary hormonal deficiencies may cause life-threatening metabolic and systemic complications. Early recognition and multidisciplinary management are therefore essential to prevent permanent sequelae and optimize functional recovery. Case DescriptionA 40-year-old woman presented with a one-year history of recurrent headaches accompanied by progressive blurring of vision, diplopia, and visual field defects. She also reported irregular menstruation and unintended weight loss. Brain magnetic resonance imaging demonstrated a 2.13 × 2.28 × 3.05 cm pituitary macroadenoma with a characteristic “snowman appearance” compressing the optic chiasm. Hormonal evaluation revealed secondary adrenal insufficiency, hypogonadotropic hypogonadism, suppressed thyroid-stimulating hormone (TSH) with elevated free thyroxine (T4), and hyperprolactinemia attributed to the stalk effect, consistent with hypopituitarism and thyroid dysfunction. Initial stabilization with hydrocortisone and methimazole was performed prior to definitive management. The patient subsequently underwent transsphenoidal tumor resection with appropriate perioperative glucocorticoid coverage. Postoperatively, she remained clinically stable with improvement in headache and visual symptoms, and continued hormonal therapy under close endocrinological supervision. ConclusionsThis case underscores the importance of comprehensive hormonal assessment, timely neurosurgical intervention, and coordinated multidisciplinary care in managing pituitary macroadenomas complicated by optic chiasm compression and hypopituitarism to achieve favorable clinical outcomes.